Fluorescent Inhibitors as Tools To Characterize Enzymes: Case Study of the Lipid Kinase Phosphatidylinositol 4-Kinase IIIβ (PI4KB) - Humpolickova, Jana; Mejdrová, Ivana; Matousova, Marika; Nencka, Radim; Boura, Evzen (Journal of medicinal chemistry, 2017)
The lipid kinase phosphatidylinositol 4-kinase IIIβ (PI4KB) is an essential host factor for many positive-sense single-stranded RNA (+RNA) viruses including human pathogens hepatitis C virus (HCV), Severe acute respiratory syndrome (SARS), coxsackie viruses, and rhinoviruses. Inhibitors of PI4KB are considered to be potential broad-spectrum virostatics, and it is therefore critical to develop a biochemical understanding of the kinase. Here, we present highly potent and selective fluorescent inhibitors that we show to be useful chemical biology tools especially in determination of dissociation constants. Moreover, we show that the coumarin-labeled inhibitor can be used to image PI4KB in cells using fluorescence-lifetime imaging microscopy (FLIM) microscopy.
Keywords: fluorescenční barviva; HeLa Cells; Enzyme Inhibitors; Humans; simulace molekulového dockingu; fosfotransferasy s alkoholovou skupinou jako akceptorem; Molecular Docking Simulation; Phosphotransferases (Alcohol Group Acceptor); HeLa buňky; lidé; Fluorescent Dyes; inhibitory enzymů